Association of Isolated Coronary Microvascular Dysfunction With Mortality and Major Adverse Cardiac Events: A Systematic Review and Meta‐Analysis of Aggregate Data. Issue 9 (5th May 2020) - Gdowski, Mark A.; Murthy, Venkatesh L.; Doering, Michelle; Monroy‐Gonzalez, Andrea G.; Slart, Riemer; Brown, David L.
Abstract : Background: The impact of coronary microvascular dysfunction (CMD), as diagnosed by reduced coronary flow reserve, on the outcomes of patients with symptoms of myocardial ischemia and nonobstructive coronary artery disease is poorly understood. We performed a systematic review and meta‐analysis of observational studies to determine the association of CMD with outcomes. Methods and Results: We searched online databases for studies where coronary flow reserve was measured invasively or noninvasively, clinical events were recorded after determination of coronary flow reserve, and the frequency of those events was reported for patients with and without CMD. The primary outcome was all‐cause mortality. The secondary outcome was major adverse cardiac events, including cardiac or cardiovascular death, nonfatal myocardial infarction, cardiac hospitalization, or coronary revascularization. Estimates of effect were calculated from crude event rates with a random‐effects model. There were 122 deaths in the 4661 patients without CMD (2.6%) and 183 deaths in the 1970 patients with CMD (9.3%). The odds ratio for mortality in patients with CMD compared with those without CMD was 3.93 (95% CI, 2.91–5.30; P <0.001). There were 167 major adverse cardiac events in the 3742 patients without CMD (4.5%) and 245 events in the 1447 patients with CMD (16.9%). The odds ratio for major adverse cardiac events in patients with CMD compared with those without CMD was 5.16 (95% CI, 2.81–9.47; P <0.001). Conclusions: CMD is associated with a nearly 4‐fold increase in mortality and a 5‐fold increase in major adverse cardiac events. Future studies are needed to identify effective strategies to diagnose and treat CMD.